Laser-microEDM based hybrid micromachining: microdrilling and micromilliling - Saleh, Tanveer; Noor Rashid, Mir Akmam; Wan Azhar, Wan Ahmad; Ibne Noor, Wazed (Springer Nature, 2024)
This book covers the various aspects of laser micromachining (LBMM) and micro electro-discharge machining (uEDM) sequential hybrid process. LBMM-mEDM-based hybrid micromachining is a growing interest among researchers because of its unique features to harness the advantages of the two primary methods. This book guides the readers to implement this LBMM-mEDM-based hybrid process for the micromachining process efficiently to achieve a higher production rate with improved machining quality. It will provide the basic understanding about the LBMM-mEDM process, how the primary process's parameters affect the overall performance of the hybrid machining's outcome, how the hybrid process can be mathematically modelled to describe various observed phenomena of the said micromachining method. This book caters to researchers and industrial practitioners who are interested in precision and high throughput machining.